ANALISIS ANGKET KEBUTUHAN PESERTA DIDIK DI SMPN 3 SELONG DALAM KEGIATAN LAYANAN BIMBINGAN DAN KONSELING - Ilmi, Nurul; Aulia, Fitri; Yulianti, Dewi (Universitas Hamzanwadi, 2024)
Student needs questionnaire is one of the instruments used by guidance and counseling teachers to determine the needs of students in order to design programs and carry out guidance and counseling service activities. The program in question needs to be analyzed to obtain accurate information. The research method used is quantitative with a descriptive approach. The sampling technique used is saturated sampling. The sample involved in the study was 17 students of SMPN 3 Selong VII C. The focus of data collection was using the Student Needs Questionnaire (AKPD) consisting of 50 problem statement items. The collected data was analyzed using computer-based AKPD. The results showed class profile data per problem area, namely personal aspects 40.78%, social aspects 23.18%, career aspects 15.92%, and learning aspects 20.11%. The results of this percentage explain that grade VII junior high school students have the highest problems in the personal field, namely feeling inferior, not having the habit of being honest, managing emotions well, not having the ability to know and be responsible for themselves.